Application of a decision model by using an integration of AHP and TOPSIS approaches within humanitarian operation life cycle - Krittiya Saksrisathaporn (2018)
© 2016 World Scientific Publishing Company. Emergency logistics is one of the most important parts of disaster relief operations. Quick and adequate decision making in this sector is vital but sometimes hard to achieve. This issue is currently faced by several humanitarian organizations, where the high turnover of staff and the lack of adequate tools make it hard to learn from past experiences. Choosing the most appropriate supplier, the adapted warehouse and transportation means is a complicated task. Indeed, on the one hand there are many criteria to take into account in the decision-making process, and on the other hand the relative importance of those criteria is changing over time. Existing academic works on this issue are very difficult to implement on real case scenarios as they do not propose practical solutions. In this paper, a decision model which evolves over time, depending on operations progresses is proposed. Selection of supplier, warehouse and vehicle are taken into consideration thanks to the Multi-Criteria Decision Making (MCDM) approach. In order to achieve a proper decision, Analytic Hierarchy Process (AHP) is used first to analyze the structure of alternatives selection problem and to determine weights of criteria. Then Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method is used to obtain final ranking in a four-phases of humanitarian operation life cycle. A numerical example based on preliminary data from the French Red Cross including the sensitivity analysis is presented to clarify and validate the methodology.